2019
DOI: 10.3390/app9183732
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Removal from Water by Adsorption onto Iron Oxide/Nano-Porous Carbon Magnetic Composite

Abstract: This study aimed to develop magnetic Fe3O4/sugarcane bagasse activated carbon composite for the adsorption of arsenic (III) from aqueous solutions. Activated carbon (AC) was prepared from sugarcane bagasse by chemical activation using H3PO4 as an activating agent at 400 °C. To enhance adsorption capacity for arsenic, the resultant AC was composited with Fe3O4 particles by facile one-pot hydrothermal treatment. This method involves mixing the AC with aqueous solution of iron (II) chloride tetrahydrate, polyviny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(41 citation statements)
references
References 41 publications
5
34
0
Order By: Relevance
“…Although the time required to reach the equilibrium sorption is slightly longer in oxidized PET (360 min) compared with the pristine counterpart (300 min), this is far from a problem given the high amount of equilibrium adsorption obtained. The relative distribution of As(III) species and the ionization of functional groups on the adsorbent surface depend on the pH of the solution [53,54]. When the effect of pH on As(III) sorption was examined, it was found that the maximum sorption capacity was obtained at pH 4 (Figure 4).…”
Section: Sorption Kinetics Of As(iii) On Composite Temsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the time required to reach the equilibrium sorption is slightly longer in oxidized PET (360 min) compared with the pristine counterpart (300 min), this is far from a problem given the high amount of equilibrium adsorption obtained. The relative distribution of As(III) species and the ionization of functional groups on the adsorbent surface depend on the pH of the solution [53,54]. When the effect of pH on As(III) sorption was examined, it was found that the maximum sorption capacity was obtained at pH 4 (Figure 4).…”
Section: Sorption Kinetics Of As(iii) On Composite Temsmentioning
confidence: 99%
“…When the effect of pH on As(III) sorption was examined, it was found that the maximum sorption capacity was obtained at pH 4 (Figure 4). The relative distribution of As(III) species and the ionization of functional groups on the adsorbent surface depend on the pH of the solution [53,54]. When the effect of pH on As(III) sorption was examined, it was found that the maximum sorption capacity was obtained at pH 4 (Figure 4).…”
Section: Sorption Kinetics Of As(iii) On Composite Temsmentioning
confidence: 99%
“…At this point, we need to compare our results with the results for previously reported filters. Indeed, various adsorbents have been used to remove As (III) [47][48][49][50][51]. As can be seen in Table 1, the iron (III) oxide used as an absorbent in the 3D, printed PLA filter in this study showed superior performance with a higher maximum adsorption capacity of As (III) than the adsorbents used in the previously reported studies.…”
Section: Plos Onementioning
confidence: 67%
“…Isotherm coefficient (L/mg) of adsorption of cadmium were bo=0.0038 (JP) and bo=0.0048 (AT) for Langmuir were whereas for Freundlich model Kf was 2.98(L g −1 ) for JP and 2.63(L g −1 ) for AT. For the Temkin model constants were bT = 3140.30 (J mol −1 ), KT= 47.47(L g −1 ) for AT and bT = 3205.37 (J mol −1 ), KT= 4.27 (L g −1 ) JP, respectively [Yao et al 2014;Joshi et al 2019;Idreeset al 2018]. The calculated qm values that reflect the adsorption of cadmium on the JP and AT adsorbent for Langmuir isotherm 3191.50 mg/g and 1886.80 mg/g, respectively, which are veryclose to the experiment results and much higher than previously reported biomaterials given in Table 3.…”
Section: Kinetics Study and Equilibrium Isotherm Of Java Plum Seed Anmentioning
confidence: 99%